HUBUNGAN RIWAYAT PERSALINAN DENGAN TINDAKAN DENGAN KEJADIAN POSTPARTUM BLUES PADA IBU NIFAS DI PUSKESMAS WARA KOTA PALOPO - Yuniar Dwi Yanti; Farida Farida (Bina Generasi : Jurnal Kesehatan, 2022)
Background: Postpartum blues is one of three categories of psychological disorders in the postpartum period. Symptoms caused by mothers are easy to cry, feel lost, feel they have more responsibility, fatigue, unstable mood and difficulty concentrating, and feelings of mothers who are more sensitive to irritability. In addition, postpartum blues can also lead to disturbances in eating and sleeping patterns in postpartum mothers. In various references, it is stated that the onset of postpartum blues is influenced by several factors, including a history of childbirth. Objective: This research is aimed to analyze the relationship between a history of normal delivery with intervention with the incidence of postpartum blues in postpartum mothers in the working area of The Public Health Center of Wara of Palopo City. Method: This research is quantitative research with an analytical survey method using cross-sectional study approach. The sample is the seventh to the fourteenth day of postpartum mothers with accidental sampling technique with a total sample of 31 people. Data analysis using Chi-Square test with a degree of significance 95% (α=0.05). Result: There is a significant relationship between the history of normal delivery with intervention with the incidence of postpartum blues in postpartum mothers at the Public Health Center of Wara, Palopo City (p = 0.014). Conclusion: A history of normal delivery with good measures of labor induction, rupture, and episiotomy is associated with the incidence of postpartum blues in postpartum mothers at the Public Health Center of Wara, Palopo City.